Analisis Sistem Informasi Akuntansi Pengumpulan Zakat di Badan Amil Zakat Nasional (BAZNAS) Kabupaten Mempawah: Analisis Sistem Informasi Akuntansi Pengumpulan Zakat di Badan Amil Zakat Nasional (BAZNAS) Kabupaten Mempawah - syafitri, inda afria; Yulia, Yulia; Ningrum, wulan wahyu (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2020)
This study aims to determine how the Accounting Information System for Zakat Collection at the National Amil Zakat Agency (BAZNAS) of Mempawah Regency. To achieve the expected goals in this study, researchers used descriptive qualitative methods. The data collection techniques used are: observation, interview, and documentation. The data studied was obtained from the zakat collection report made by the zakat distribution section of BAZNAS Mempawah Regency. The result of this research is that BAZNAS Mempawah Regency still uses the old system, which is using manual recording system in its financial reporting. The system of recording, receiving, and distributing ZIS funds made is still not in accordance with relevant accounting policies. The advice given by researchers to BAZNAS is that the financial statements of BAZNAS Mempawah Regency should implement a web-based accounting information system to make it easier for the public to access the financial reporting system. As we know that the IAI (Indonesian Accounting Association) issued PSAK 109 in order to become the basis for amil zakat institutions in preparing and presenting the expected financial statements.